Proceedings of the 8th International Conference on Intelligent User Interfaces 2003
DOI: 10.1145/604045.604066
|View full text |Cite
|
Sign up to set email alerts
|

Presenting route instructions on mobile devices

Abstract: In this paper, we evaluate several means of presenting route instructions to a mobile user. Starting from an abstract languageindependent description of a route segment, we show how to generate various presentations for a mobile device ranging from spoken instructions to 3D visualizations. We then examine the relationship between the quality of positional information, available resources and the different types of presentations. The paper concludes with guidelines that help to determine which presentation to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(73 citation statements)
references
References 13 publications
(13 reference statements)
3
69
1
Order By: Relevance
“…In an evaluation of alternative methods of presenting route instructions on mobile devices, Kray et al (2003) revealed that in order to find their current location on a 2D map, users often found that a 3D view was useful in identifying their location in the real world. This study also confirmed a finding of several other studies, which is that although the 3D display did not improve task performance, it was found to be 'fun' to use.…”
Section: Multiple Linked Viewsmentioning
confidence: 99%
“…In an evaluation of alternative methods of presenting route instructions on mobile devices, Kray et al (2003) revealed that in order to find their current location on a 2D map, users often found that a 3D view was useful in identifying their location in the real world. This study also confirmed a finding of several other studies, which is that although the 3D display did not improve task performance, it was found to be 'fun' to use.…”
Section: Multiple Linked Viewsmentioning
confidence: 99%
“…These include linguistic (text and verbal), map, sketch, tactile and augmented-reality representations [31,41]. Due to their ubiquity, linguistic representations are by far the most commonly studied.…”
Section: Route Descriptions -Information and Representationmentioning
confidence: 99%
“…Registering a route to a street network can simplify the problem of converting to an alternative representation. To demonstrate this we propose a simple algorithm which converts a route registered to a street network to a set of turn-by-turn instructions; specifically, the set of turn-by-turn instructions generated are path relations [31].…”
Section: Conversion Of Interactive Route Descriptionmentioning
confidence: 99%
“…Mobile devices have been used to enhance the presentation of different kinds of spatial information, such as landmarks (Sefelin et al 2005;Goodman et al 2004;May et al 2003), route information (Kray et al 2003;Narzt et al 2003;Malaka and Zipf 2000), as well as maps. However, these designs usually focus on just one particular type of spatial information, and do not consider their integration, which is important to the construction of cognitive maps.…”
Section: Using Mobile Devices To Support Navigationmentioning
confidence: 99%